2019
DOI: 10.1080/17518253.2019.1629698
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of 1018 carbon steel using an avocado oil-based inhibitor

Abstract: The corrosion phenomenon in oil and gas industry is a serious issue affecting metallic structures and pipelines. The main aggressive species flowing through oil pipelines is NaCl. The presence of gases in the corrosive medium (CO 2 and H 2 S), increases, even more, its aggressiveness. Usually, to mitigate corrosion, liquid inhibitors are added to the corrosive medium. In the present study, N-hydroxyethyl-imidazoline derivatives of avocado oil was synthesized as a green corrosion inhibitor. The test was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The vast majority of these studies investigated extracts obtained from various parts of plants, including roots, [31a] bark, [101] leaves, [30c,31b,78–79,90,112‐113] seeds, [30d,79e] and fruits (including the peel of certain fruits) [30c,71c,79b,88a–c,143] as CIs for steel in a CO 2 environment (Table S9 in Supplementary Material). It was also reported that natural products are used to either synthesize [37,104–105,107c,118b,119‐120,131a‐c,e,144] or modify other compounds [128c,f,131d] that have been tested as CIs in a CO 2 environment (Table S10 in Supplementary Material). In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of these studies investigated extracts obtained from various parts of plants, including roots, [31a] bark, [101] leaves, [30c,31b,78–79,90,112‐113] seeds, [30d,79e] and fruits (including the peel of certain fruits) [30c,71c,79b,88a–c,143] as CIs for steel in a CO 2 environment (Table S9 in Supplementary Material). It was also reported that natural products are used to either synthesize [37,104–105,107c,118b,119‐120,131a‐c,e,144] or modify other compounds [128c,f,131d] that have been tested as CIs in a CO 2 environment (Table S10 in Supplementary Material). In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…In order to evaluate the corrosion inhibition effectiveness of these natural products, steel samples were immersed in either NaCl solutions, [30c,d,31,37,67c,71c,77,79a–e,88a‐c,94,107c,112‐113,118b,120,128f,131c‐e,143‐144] brine and simulated oilfield waters, [58,84,90,117,119] or emulsions consisting of a combination of 3 wt.% NaCl solution and diesel at different volume ratios [105,128c,131a,b,145] . Souza et al [30a] .…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…The inhibition efficiency reached 98.2%, the highest value, at the end of the 72 h exposure period with solutions containing 5.0×10 -5 and 1.0×10 -4 M DMT, and after this hour (72 h), the decrease with time was marked in the inhibition values ( Table 2). The time-dependent decrease in the inhibition efficiency is due to the gradual oxidative dissolution of the mild steel in prolonged contact with the corrosive medium and the corrosive effect of chloride ions adsorbable to the inner-Helmholtz layer at the metal-solution interface and the composition of the solution changing near the metallic surface [26][27][28][29][30]. However, at the end of the 120 h exposure period, it is apparently seen that the inhibitor film on the metal/solution interface has begun to be deteriorated and dispersed the frequency, but the protection of the solution containing the DMT inhibitor at the highest concentration is still 93.0%.…”
Section: Eis Lpr and Potentiodynamic Polarization Experimentsmentioning
confidence: 99%
“…At the same time, jcorr value was decreased for 2 orders of magnitude. Sotelo-Mazon et al [32] obtained IE of 99 % with imidazoline synthesized from wasted avocado oil for carbon steel in CO2-saturated 3.5 % NaCl solution, and jcorr value was reduced for 2 orders of magnitude, from 0.1 to 0.001 mA cm -2 . Okafor et al [33] obtained an inhibitor efficiency of 97 % with the addition of 200 ppm of a rosin amide imidazoline for N80 carbon steel in CO2saturated simulated formation water, with the reduction of jcorr value from 0.1 down to 0.005 mA cm -2 .…”
Section: Polarization Curvesmentioning
confidence: 99%
“…It is seen in Figure 8b that capacitive impedances increased (capacitance decreased) with the addition of inhibitor up to 25 ppm, and decreased (capacitance increased) for higher inhibitor concentrations. It has already been known that two different electric interface values, such as electrical resistance and capacitance, are inversely proportional [37][38][39][40][41][42][43], and thus, an increase in the resistance value decreases the capacitance value. This proves the ability of the studied extract to reduce the aggressive action of the acid medium.…”
Section: Eis Measurementsmentioning
confidence: 99%